(untitled) (Bioagro, 2024)
Phosphorus is considered the most limiting essential macronutrient for plant production in soils of tropical climates. As the chemical and physical properties of the soil influence the availability of P to crops, the use of suitable extractants can increase the precision of the results obtained in soil analysis to enable the maximization of the efficiency of using phosphate fertilizers in agriculture. With this, the objective was to evaluate the capacity of the Mehlich-1 (M1) and Mehlich-3 (M3) extractors to determine the extractable P content in the soil in agricultural areas fertilized with liquid swine manure. The sampled sites were under the sandy loam (Sl) and sandy (S) textural class and were separated into four plots (repetitions) of 15 hectares each, where soil samples were collected in three depths 0.00-0.05; 0.05-0.10; and 0.10-0.20 m. For a depth of 0.20 m, the average levels of extractable P found in the evaluated textural classes were 34.83 (Sl) and 12.56 mg·dm-3 (S) for extractor M1; and 2.91 (Sl) and 0.81 mg·dm-3 (S) for extractor M3. It is clear that, although the Mehlich-1 solution has a greater capacity to extract the P content than the Mehlich-3 solution, both extractants can be used to extract the P content in sandy loam/sandy soils fertilized with liquid swine manure in the Cerrado region of Mato Grosso (Brazil).